The transcription factor E4bp4/Nfil3 controls commitment to the NK lineage and directly regulates Eomes and Id2 expression - Male,V; Nisoli,I; Kostrzewski,T; Allan,DSJ; Carlyle,JR; Lord,GM; Wack,A; Brady,HJM (Journal of Experimental Medicine, 2014)
The transcription factor E4bp4 (Nfil3) is essential for natural killer (NK) cell production. Here, we show that E4bp4 is required at the NK lineage commitment point when NK progenitors develop from common lymphoid progenitors (CLPs) and that E4bp4 must be expressed at the CLP stage for differentiation toward the NK lineage to occur. To elucidate the mechanism by which E4bp4 promotes NK development, we identified a central core of transcription factors that can rescue NK production from E4bp4−/− progenitors, suggesting that they act downstream of E4bp4. Among these were Eomes and Id2, which are expressed later in development than E4bp4. E4bp4 binds directly to the regulatory regions of both Eomes and Id2, promoting their transcription. We propose that E4bp4 is required for commitment to the NK lineage and promotes NK development by directly regulating the expression of the downstream transcription factors Eomes and Id2.